ON PUBLIC MONITORING OF NORMATIVE LEGAL ACTS - Erlan Kadirzhanovich, Ахметов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
This article is an attempt to reveal the concept of "public monitoring" of normative legal acts, as well as its relation with the notions of "public control" and "public monitoring of the quality of public services"